2013
DOI: 10.1016/j.bmc.2013.03.027
|View full text |Cite|
|
Sign up to set email alerts
|

Geranylated flavonoids displaying SARS-CoV papain-like protease inhibition from the fruits of Paulownia tomentosa

Abstract: SARS-CoV papain-like protease (PLpro) is an important antiviral target due to its key roles in SARS virus replication. The MeOH extracts of the fruits of the Paulownia tree yielded many small molecules capable of targeting PLpro. Five of these compounds were new geranylated flavonoids, tomentin A, tomentin B, tomentin C, tomentin D, tomentin E (1-5). Structure analysis of new compounds (1-5) by NMR showed that they all contain a 3,4-dihydro-2H-pyran moiety. This chemotype is very rare and is derived from cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(146 citation statements)
references
References 12 publications
1
142
0
3
Order By: Relevance
“…2). This suggests that increasing inhibitor concentration led to a decrease in V max and an increase in K m (Cho et al 2013), indicating that compounds 2 and 5-7 were mixed-type inhibitors. The K i values of compounds 1-7 were also measured using Dixon plots ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…2). This suggests that increasing inhibitor concentration led to a decrease in V max and an increase in K m (Cho et al 2013), indicating that compounds 2 and 5-7 were mixed-type inhibitors. The K i values of compounds 1-7 were also measured using Dixon plots ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…18) Several geranyl-substituted flavanones that were isolated from P. tomentosa as minor components showed inhibitory activity against papain-like protease of coronavirus of severe acute respiratory syndrome (SARS). 19) As polyphenolic compounds, the activity of flavonoids is commonly attributed to their antioxidant, anti-inflammatory activities. 20) We showed that the antiviral effect of apigenin against EV71 infection was unlikely related to the antioxidant properties since similar compounds failed to inhibit EV71 infection.…”
Section: )mentioning
confidence: 99%
“…The antioxidant Š mejkal et al 2007a, b;Zima et al 2010), antibacterial (Navrátilová et al 2013;Š mejkal et al 2008b), antiphlogistic , cytotoxic (Kollár et al 2011;Š mejkal et al 2007a, and severe acute respiratory syndrome coronavirus papain-like protease (SARS-CoV PLpro) activities (Cho et al 2013) of isolated geranylated flavonoids have been described recently, together with their inhibitory effect on both human acetylcholinesterase and butyrylcholinesterase (Cho et al 2012). The great ability of several geranylated flavanones to interact with bacterial sialidase isolated from Clostridum perfringens (Cp-NanI), a bacterium causing various gastrointestinal diseases, has recently been reported (Lee et al 2014).…”
Section: P Tomentosa Flavonoids and Their Biological Activitymentioning
confidence: 99%
“…Prenylated flavonoids 55-59, modified with an unusual 3,4-dihydro-2H-pyran moiety, have been found to inhibit the severe acute respiratory syndrome corona virus PLpro enzyme more effectively than their parent compounds, the precursors from which were they derived (Cho et al 2013).…”
Section: P Tomentosa Flavonoids and Their Biological Activitymentioning
confidence: 99%